2014
DOI: 10.1002/pbc.25050
|View full text |Cite
|
Sign up to set email alerts
|

False positivity of ETV6/RUNX1 detected by FISH in healthy newborns and adults

Abstract: The leukemia-associated ETV6-RUNX1-translocation frequently emerges prenatally. Reverse-transcriptase PCR screening may indicate presence of ETV6-RUNX1 transcripts in random cord blood samples. Subsequent cell enrichment validation finds significantly lower levels than validation applying fluorescence in situ hybridization (FISH) (<10(-5) vs. 10(-3) to 10(-4)). Using three FISH probe sets, we screened 179,000 cells from ETV6-RUNX1-positive dilution series, healthy adults and random cord blood samples. The t(12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Initially identified in umbilical cord blood of one healthy newborn and the peripheral blood of 13 healthy children and adults [32], ETV6-RUNX1 was shown to be present in~1% of newborns [6]. Several Danish studies later challenged these findings [36,[44][45][46][47], but newer reports confirmed the original results [7,[37][38][39].…”
Section: Etv6-runx1mentioning
confidence: 95%
“…Initially identified in umbilical cord blood of one healthy newborn and the peripheral blood of 13 healthy children and adults [32], ETV6-RUNX1 was shown to be present in~1% of newborns [6]. Several Danish studies later challenged these findings [36,[44][45][46][47], but newer reports confirmed the original results [7,[37][38][39].…”
Section: Etv6-runx1mentioning
confidence: 95%
“…However, there were possibilities that RT-PCR and FISH produce false positive results due to technical problems although it might be rare, [33][34][35][36][37][38] and that not all the best probes and primers for known fusion genes with optimal conditions were used in all 13 cases. Thus, we are still unable to definitively conclude that all thirteen reported cases were primary CCS of the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a technical detail deserves mentioning that in recent years fusion genes are not usually studied using traditional hybridization-based techniques such as FISH (fluorescent in-situ hybridization) and southern blots but, instead, are mainly studied using RT-PCR and RNA-seq technologies that detect fusion RNAs, but not fusion genes per se . RT and PCR may create many artifacts, as to be discussed later, making it possible that some so detected are artifacts 75 , 94 , 100 , 101 . Also, in many cases it is actually unclear whether the detected chimeric RNAs, even if they are authentic, are associated with a corresponding fusion gene or are just formed at the RNA level.…”
Section: From Fusion Rna To Fusion Gene: the Cart Before The Horse Inmentioning
confidence: 99%